In situ experiments and seismic analysis of existing buildings, Part I Experimental investigations. - Hans, S. (Earthquake engineering & structural dynamics.)
Recent results of in situ measurements and their interest for a seismic assessment of existing buildings are presented and analysed. The present paper (Part I) is devoted to the experimental programme. The response to ambient vibrations, harmonic excitation and shock loading is recorded on intact buildings but also their structure or their vicinity was modified. These tests aim to identify the dynamic behaviour of ordinary intact buildingsw built in a conventional practise. Moreover, taking advantage of their demolition, it was possible (through these tests) to determine the actual influence of the light work elements, full precast facade panels, bearing masonry walls, and the presence of neighbouring joined buildings. These experiments realized on real buildings show that information gathered from ambient measurements provide reliable and efficient data of real interest for a clear understanding of the actual building behaviour. The advantage of integrating these data in the vulnerability assessment is presented and discussed in the next paper (Part II).